Manajemen Pengembangan Kurikulum dalam Pendidikan Islam di MTs Negeri 1 Barito Timur - silaningtyas, yuniar (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2024)
This research aims to determine the management of curriculum development at MTs Negeri 1 Barito Timur.  The research method used is descriptive research using a qualitative approach. Data collection techniques are through observation, interviews, and documentation studies. The results of this research show that MTs Negeri 1 East Barito has carried out curriculum development with a process of (1) planning carried out by the Head of the Madrasah with the assistance of the Deputy Head of the Madrasah, (2) implementation of curriculum development carried out through the learning process in class which refers to the syllabus and RPP, (3) the results of curriculum development in the form of additions to the RPP and the learning process in class, (4) evaluation of curriculum development by the madrasa head is carried out within one semester and evaluation by study teachers is carried out after each learning process Keywords: management, curriculum, madrasah